Juridical Analysis of Legal Protection From the Witness and Victim Protection Agency (LPSK) - Waliadin Waliadin*; Liza Nofianti (Universitas Syiah Kuala, 2021)
Law No. 31 of 2014 on witness and Victim Protection (Article 1) states that LPSK is an institution tasked and authorized to provide protection and other rights to witnesses and/or victims as stipulated in the law. And in Article 12 states LPSK is responsible for handling the provision of protection and assistance to witnesses and victims based on the duties and authorities as stipulated in the law. In certain circumstances, protection may be granted shortly after the application is submitted to LPSK. The factor of lack of socialization for people in the area is the weakness of LPSK's performance development, although currently in 2023 LPSK has stated that it has provided various channels, ranging from application applications available on Android, services via Whatsapp, email, letters.